(untitled) (Ciudades, 2017)
The two last decades have consolidated a type of urban construction based on the great investment of the collective surplus value in the whole city, pursuing the exclusivity of the city or, also, in one of its areas. As a consequence, local institutions supported the lost of its economic capacity. The investment in the urban centre has not expected one social or territorial balance, aggravating the dispossession of popular classes and producing a fetish space around the consumption. Madrid has supported, in its physical space, a great accumulation of collective surplus value, in the form of infrastructures and operations about the urban scene, that have increased the local debt. Also, these surplus value have contributed to the consolidation of the excellence and prestige discourse of the urban centre. The city has been transformed into the show window of a space produced for the merchandise and capital change. The investment allows the reproduction of the globalisation ways of life, which are based on the appearance and the prestige of the social mobility.